Meloxicam vs robenacoxib for postoperative pain management in dogs undergoing combined laparoscopic ovariectomy and laparoscopic‐assisted gastropexy. Issue 4 (13th January 2019) - Bendinelli, Cristiano; Properzi, Roberto; Boschi, Paolo; Bresciani, Carla; Rocca, Erica; Sabbioni, Alberto; Leonardi, Fabio
Abstract: Objective: To compare meloxicam and robenacoxib for short‐term postoperative pain management after combined laparoscopic ovariectomy and laparoscopic‐assisted gastropexy. Study design: Double‐blind, prospective, randomised clinical trial. Animals: Twenty‐six client‐owned female dogs. Methods: Dogs undergoing combined laparoscopic ovariectomy and laparoscopic‐assisted gastropexy were randomly divided into 2 groups. Before induction of anesthesia, 13 dogs received meloxicam (0.2 mg/kg subcutaneously), and 13 dogs received robenacoxib (2 mg/kg subcutaneously). Pain was scored with the Glasgow Composite Pain Scale (short form) before surgery and at 1, 6, 12, 18, and 24 hours after extubation. Rescue analgesia (tramadol, 3 mg/kg) was provided to dogs with a Glasgow pain score (GPS) ≥5. Glasgow pain scores were analyzed by ANOVA with treatment, age, and surgical time as fixed factors. Results: Glasgow pain scores were higher at 24 hours postsurgery in dogs treated with robenacoxib (2.18 ± 0.29) compared with those treated with meloxicam (0.68 ± 0.41, P  = .04). Two dogs treated with meloxicam and 7 dogs treated with robenacoxib required rescue analgesia. Regardless of the treatment, the overall GPS was lower at 18 and 24 hours postsurgery when the surgical time was >40 minutes compared with surgical times ≤40 minutes, but surgical site inflammation was likely a confounding factor in this finding. Glasgow pain score was not affected by patient age. Conclusion: Meloxicam was more effective than robenacoxib at controlling pain in the population of dogs reported here. Clinical significance: Preoperative administration of meloxicam effectively controls pain for 24 hours after combined laparoscopic ovariectomy and laparoscopic‐assisted gastropexy, but rescue analgesia may be required.